Intrathecal magnetic drug targeting using gold-coated magnetite nanoparticles in a human spine model. (August 2014) - Lueshen, Eric; Venugopal, Indu; Kanikunnel, Joseph; Soni, Tejen; Alaraj, Ali; Linninger, Andreas
Aim: We aimed to magnetically guide and locally confine nanoparticles in desired locations within the spinal canal to achieve effective drug administration for improved treatment of chronic pain, cancers, anesthesia and spasticity.Materials & methods: We developed a physiologically and anatomically consistent in vitro human spine model to test the feasibility of intrathecal magnetic drug targeting. Gold-coated magnetite nanoparticles were infused into the model and targeted to specific regions using external magnetic fields. Experiments and simulations aiming to determine the effect of key parameters, such as magnet strength, duration of magnetic field exposure, magnet location and ferrous implants, on the collection efficiency of superparamagnetic nanoparticles in targeted regions were performed.Results: An 891% increase in nanoparticle collection efficiency within the target region was achieved using intrathecal magnetic drug targeting when compared with the control. Nanoparticle collection efficiency at the target region increased with time and reached a steady value within 15 min. Ferrous epidural implants generated sufficiently high-gradient magnetic fields, even when magnets were placed at a distance equal to the space between a patient's epidermis and spinal canal.Conclusion: Our experiments indicate that intrathecal magnetic drug targeting is a promising technique for concentrating and localizing drugs at targeted sites within the spinal canal for treating diseases affecting the CNS. Original submitted 27 June 2012; Revised submitted 11 March 2013